COVID‐19 modeling in Sub‐Saharan Africa - Mueller, Valerie; Sheriff, Glenn; Keeler, Corinna; Jehn, Megan (Agricultural and Applied Economics Association, 2021)
After an initial delay, Sub‐Saharan Africa (SSA) is being hit by the pandemic. Demand for exports is falling and caseloads are rising. Governments have approached this crisis with a range of policy options. Optimal policy balances reduced infection rates with lost economic output. This paper discusses how an economic‐epidemiological model used to analyze policy in high‐income countries could be adapted to a context where poverty considerations are paramount. Differences in country characteristics across the continent affect benefits and costs of alternative policy designs. We conclude by highlighting data needs and model calibration challenges for COVID‐19 policy research in SSA.